Preparation method of high-specific-stiffness composite wire

Beryllium/aluminum composite materials were prepared by self-exhaust pressure impregnation method, and copper-clad composite wires were prepared in combination with hot extrusion and hot drawing processes, which solved the problems of high density, specific stiffness and strength of wire materials, and achieved low density, high specific stiffness and high conductivity composite wires to meet the high performance needs of the aerospace field.

CN119650189AActive Publication Date: 2025-03-18HARBIN INST OF TECH +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411842262.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-18
Estimated Expiration
2044-12-13

AI Technical Summary

Technical Problem

Existing wire materials are high in density, low specific stiffness and strength in the aerospace field, and cannot meet the needs of high-performance applications.

Method used

The beryllium/aluminum composite material was prepared by self-exhaust pressure impregnation method, and the copper-clad beryllium/aluminum composite composite wire was prepared by hot extrusion and hot drawing process to form a metallurgical bond to improve the interface bonding strength.

Benefits of technology

The copper-clad beryllium/aluminum composite composite wire with low density, high specific stiffness and high conductivity is realized, which meets the high performance needs of the aerospace field and provides an efficient and low-cost preparation method.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119650189A_ABST
    Figure CN119650189A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of a composite wire, in particular to a preparation method of a high-specific-stiffness composite wire. The invention aims to solve the problems of high density, low specific stiffness and low strength of the existing lead. The beryllium / aluminum composite material bar subjected to hot extrusion is subjected to sheathing treatment, a multi-pass drawing method is adopted at the high temperature, the copper element is diffused into the beryllium / aluminum composite material at the core part, metallurgical bonding is formed, high interface bonding strength is achieved, and the low-density copper-sheathed beryllium / aluminum composite material composite wire is obtained; and meanwhile, the rigidity of the wire is improved through the bearing of the beryllium / aluminum composite material inner core. According to the invention, the beryllium / aluminum composite material is used as the inner core skeleton of the composite wire, so that the reinforcing effect is achieved, and the density of the wire can be greatly reduced. The specific stiffness of the prepared high-specific-stiffness composite wire exceeds 27 GPa / (g / cm < 3 >), and the conductivity exceeds 4 * 10 < 7 > S / m.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a composite conductor with high specific stiffness. Background Art

[0002] In the aerospace field and special environments such as space, the conductivity of wires is a basic requirement, but there are also strict standards for their physical parameters such as strength, stiffness and density. These requirements are due to the operation requirements of aerospace vehicles under extreme conditions. The selection of any material must comprehensively consider its performance and application environment.

[0003] Among the commonly used wire materials, copper and aluminum are the two most widely used metals. Copper is known for its excellent electrical conductivity and can effectively conduct current. However, copper itself has a high density of 8.96g / cm 3 , which makes copper unable to meet the demand for lightweight materials. In addition, the elastic modulus of copper is 119GPa, and its specific stiffness is only 13.37GPa / (g / cm 3 ), which is far from meeting the demand for high stiffness, especially in environments subject to high loads or vibrations.

[0004] In comparison, aluminum has a lower density of only 2.7 g / cm 3 , which meets the requirements of lightweight materials. However, the elastic modulus of aluminum is only 71.7GPa, and its strength and stiffness cannot meet the needs of high-performance applications. In some precision equipment, gold and silver are widely used due to their excellent conductivity and stable chemical properties, but their densities are as high as 19.32g / cm 3 and 10.49 g / cm 3 , is not suitable as a structural material, and is expensive, which limits its feasibility in large-scale applications.

[0005] Therefore, it is urgent to develop a conductor material with a composite structure to meet the structural and functional requirements of the conductor. This composite conductor should combine the advantages of different materials, maintain good conductivity, and meet the requirements of the aerospace field in terms of strength, stiffness, and density. Through innovative material design and manufacturing processes, future composite conductors will be able to perform well in extreme environments, providing strong support for the development of aerospace technology. Summary of the invention

[0006] The purpose of the present invention is to solve the problem of high density, low specific stiffness and low strength of existing wires, and to provide a method for preparing a composite wire with high specific stiffness.

[0007] The method for preparing the high specific stiffness composite conductor of the present invention is carried out according to the following steps:

[0008] Step 1: Preparation of Be / Aluminum Composite Materials

[0009] The beryllium / aluminum composite material is prepared by a self-exhaust pressure infiltration method; the volume fraction of beryllium powder in the beryllium / aluminum composite material is 20% to 70%, and the aluminum matrix in the beryllium / aluminum composite material is pure aluminum or aluminum alloy;

[0010] Step 2: Preheating of Be / Aluminum Composite Material and Hot Extrusion Die

[0011] First, the beryllium / aluminum composite material is preheated to a temperature of 400-600°C, and then kept at a temperature of 400-600°C for 0.5h-6h; the hot extrusion die is preheated to a temperature 10°C-100°C lower than the preheating temperature of the beryllium / aluminum composite material, and then kept at the temperature for 0.5h-6h;

[0012] Step 3: Preparation of Be / Aluminum Composite Rods by Hot Extrusion

[0013] The preheated beryllium / aluminum composite material is loaded into a preheated hot extrusion die, and hot extruded by a press to obtain a beryllium / aluminum composite material rod;

[0014] Step 4: Sheathing of Be / Aluminum Composite Bars

[0015] The pure copper tube is heated to 200-600° C., and then a pure copper tube having the same inner diameter as the beryllium / aluminum composite material rod obtained in step 3 is sheathed on the outside of the rod, and the rod is naturally cooled to room temperature to obtain a copper-sheathed beryllium / aluminum composite material rod;

[0016] Step 5: Preparation of copper-clad beryllium / aluminum composite conductor by hot drawing

[0017] A drawing machine is used to perform multiple hot drawing on a copper-clad beryllium / aluminum composite material rod, the hot drawing temperature is 200-600°C, the deformation amount of each pass is 1%-10%, and the drawing rate is 10-200mm / min; after each deformation, the copper-clad beryllium / aluminum composite material is annealed to obtain a copper-clad beryllium / aluminum composite material composite wire with a diameter of 0.5-2mm.

[0018] The present invention has the following beneficial effects:

[0019] 1. The present invention performs sheathing treatment on the hot-extruded beryllium / aluminum composite material rod, and adopts a multi-pass drawing method at high temperature to diffuse copper elements into the beryllium / aluminum composite material in the core to form a metallurgical bond, thereby achieving high interface bonding strength, and obtaining a low-density copper-sheathed beryllium / aluminum composite material composite conductor. At the same time, the rigidity of the conductor is improved by the load-bearing of the beryllium / aluminum composite material inner core.

[0020] 2. The high-rigidity, low-density copper-sheathed beryllium / aluminum composite composite conductor prepared by the present invention can adjust the diameter of the inner core of the beryllium / aluminum composite material and the thickness of the copper sheath according to actual needs to obtain composite conductors with different stiffness and density; the high-specific stiffness composite conductor prepared by the present invention has a specific stiffness of more than 27GPa / (g / cm 3 ), the conductivity exceeds 4×10 7 S / m.

[0021] 3. The present invention provides a method for efficiently and at low cost to prepare a high-rigidity, low-density copper-clad beryllium / aluminum composite material composite conductor. The method has a simple process, is easy to operate, and is easy to realize industrial production and application.

[0022] 4. Beryllium / aluminum composite material has the excellent properties of high strength and low density, and is an excellent structural material. The density of beryllium / aluminum composite material is usually 2.1g / cm 3 The density of the composite wire is about 2.3×10-1.5mm, which is lower than that of pure aluminum, but the strength can reach more than 5 times that of pure aluminum, with extremely high specific strength and specific stiffness. The present invention uses the beryllium / aluminum composite material as the inner core skeleton of the composite wire to play a reinforcing role and greatly reduce the density of the wire. The electrical conductivity of beryllium is about 2.3×10 7 S / m, so the beryllium / aluminum composite material has a higher electrical conductivity. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a spectrum scanning image of copper element diffusion into beryllium / aluminum composite material. DETAILED DESCRIPTION

[0024] The technical solution of the present invention is not limited to the specific implementation modes listed below, but also includes any reasonable combination of the specific implementation modes.

[0025] Specific implementation method 1: The preparation method of the high specific stiffness composite wire of this implementation method is carried out according to the following steps:

[0026] Step 1: Preparation of Be / Aluminum Composite Materials

[0027] The beryllium / aluminum composite material is prepared by a self-exhaust pressure infiltration method; the volume fraction of beryllium powder in the beryllium / aluminum composite material is 20% to 70%, and the aluminum matrix in the beryllium / aluminum composite material is pure aluminum or aluminum alloy;

[0028] Step 2: Preheating of Be / Aluminum Composite Material and Hot Extrusion Die

[0029] First, the beryllium / aluminum composite material is preheated to a temperature of 400-600°C, and then kept at a temperature of 400-600°C for 0.5h-6h; the hot extrusion die is preheated to a temperature 10°C-100°C lower than the preheating temperature of the beryllium / aluminum composite material, and then kept at the temperature for 0.5h-6h;

[0030] Step 3: Preparation of Be / Aluminum Composite Rods by Hot Extrusion

[0031] The preheated beryllium / aluminum composite material is loaded into a preheated hot extrusion die, and hot extruded by a press to obtain a beryllium / aluminum composite material rod;

[0032] Step 4: Sheathing of Be / Aluminum Composite Bars

[0033] The pure copper tube is heated to 200-600° C., and then a pure copper tube having the same inner diameter as the beryllium / aluminum composite material rod obtained in step 3 is sheathed on the outside of the rod, and the rod is naturally cooled to room temperature to obtain a copper-sheathed beryllium / aluminum composite material rod;

[0034] Step 5: Preparation of copper-clad beryllium / aluminum composite conductor by hot drawing

[0035] A drawing machine is used to perform multiple hot drawing on a copper-clad beryllium / aluminum composite material rod, the hot drawing temperature is 200-600°C, the deformation amount of each pass is 1%-10%, and the drawing rate is 10-200mm / min; after each deformation, the copper-clad beryllium / aluminum composite material is annealed to obtain a copper-clad beryllium / aluminum composite material composite wire with a diameter of 0.5-2mm.

[0036] This embodiment has the following beneficial effects:

[0037] 1. In this embodiment, the hot-extruded beryllium / aluminum composite material rod is sheathed, and a multi-pass drawing method is adopted at high temperature to diffuse the copper element into the beryllium / aluminum composite material in the core to form a metallurgical bond, thereby achieving high interface bonding strength, and obtaining a low-density copper-sheathed beryllium / aluminum composite material composite conductor. At the same time, the rigidity of the conductor is improved by the load-bearing of the beryllium / aluminum composite material inner core.

[0038] 2. The high-rigidity, low-density copper-sheathed beryllium / aluminum composite composite conductor prepared in this embodiment can adjust the diameter of the beryllium / aluminum composite core and the thickness of the copper sheath according to actual needs to obtain composite conductors with different stiffness and density; the high-specific stiffness composite conductor prepared in this embodiment has a specific stiffness of more than 27GPa / (g / cm 3 ), the conductivity exceeds 4×10 7 S / m.

[0039] 3. This embodiment provides a method for efficiently and at low cost to prepare a high-rigidity, low-density copper-clad beryllium / aluminum composite material composite conductor. The method has a simple process, is easy to operate, and is easy to realize industrial production and application.

[0040] 4. Beryllium / aluminum composite material has the excellent properties of high strength and low density, and is an excellent structural material. The density of beryllium / aluminum composite material is usually 2.1g / cm 3 The density of the composite wire is about 2.3×10-1.5mm, which is lower than that of pure aluminum, but the strength is more than 5 times that of pure aluminum, with extremely high specific strength and specific stiffness. In this embodiment, the beryllium / aluminum composite material is used as the inner core skeleton of the composite wire to play a reinforcing role and greatly reduce the density of the wire. The electrical conductivity of beryllium is about 2.3×10 7 S / m, so the beryllium / aluminum composite material has a higher electrical conductivity.

[0041] Specific implementation method 2: This implementation method is different from specific implementation method 1 in that: the purity of the beryllium powder described in step 1 is greater than 99%, and the average particle size is 5 to 800 μm.

[0042] Specific implementation method three: This implementation method is different from specific implementation methods one or two in that: the beryllium powder in step one is in an irregular shape, a spherical shape, and beryllium turning chips, or a combination of any ratio of the two.

[0043] Specific embodiment four: This embodiment is different from any of specific embodiments one to three in that: the aluminum alloy described in step one is one of Al-Si alloy, Al-Cu alloy, Al-Mg alloy, Al-Si-Cu alloy, Al-Si-Mg alloy, Al-Cu-Mg alloy, Al-Zn-Cu alloy, Al-Zn-Mg alloy, Al-Zn-Mg-Cu alloy, Al-Be alloy, Al-Li alloy and Al-Si-Cu-Mg alloy, or any combination of several of them.

[0044] Specific embodiment 5: The difference between this embodiment and specific embodiment 4 is that the mass fraction of Si in the Al-Si alloy is 0.5% to 25%; the mass fraction of Cu in the Al-Cu alloy is 0.5% to 53%; the mass fraction of Mg in the Al-Mg alloy is 0.5% to 38%; the mass fraction of Si in the Al-Si-Cu alloy is 0.5% to 25%, and the mass fraction of Cu is 0.5% to 53%; the mass fraction of Si in the Al-Si-Mg alloy is 0.5% to 25%, and the mass fraction of Mg is 0.5% to 38%; the mass fraction of Cu in the Al-Cu-Mg alloy is 0.5% to 53%, and the mass fraction of Mg is 0.5% to 38%; the mass fraction of Zn in the Al-Zn-Cu alloy The mass fraction of Zn in Al-Zn-Mg alloy is 0.5% to 55%, and the mass fraction of Mg is 0.5% to 38%; the mass fraction of Zn in Al-Zn-Mg-Cu alloy is 0.5% to 55%, the mass fraction of Mg is 0.5% to 38%, and the mass fraction of Cu is 0.5% to 53%; the mass fraction of Be in Al-Be alloy is 0.5% to 20%; the mass fraction of Li in Al-Li alloy is 0.5% to 35%; the mass fraction of Si in Al-Si-Cu-Mg alloy is 0.5% to 25%, the mass fraction of Cu is 0.5% to 53%, and the mass fraction of Mg is 0.5% to 38%.

[0045] Specific implementation method 6: This implementation method is different from any one of specific implementation methods 1 to 5 in that: the hot extrusion rate in step 3 is 30 mm / min to 120 mm / min.

[0046] Specific implementation method seven: This implementation method is different from any one of specific implementation methods one to six in that: the extrusion ratio of the hot extrusion in step three is (5-58):1.

[0047] Specific implementation eight: This implementation differs from any one of specific implementations one to seven in that: the inner diameter of the pure copper tube in step four is 1 to 15 mm, and the outer diameter is 2 to 30 mm.

[0048] Specific embodiment nine: This embodiment differs from any one of specific embodiments one to eight in that: in step five, a drawing machine is used to perform multiple hot drawing on the beryllium / aluminum composite material rod, the hot drawing temperature is 540°C, the deformation amount of each pass is 3%, the drawing rate is 60mm / min, and the beryllium / aluminum composite material is annealed after each deformation to obtain a copper-clad beryllium / aluminum composite material composite wire with a diameter of 2mm; the annealing process is: keeping warm at 495°C for 5h.

[0049] Specific implementation method ten: This implementation method is different from any one of specific implementation methods one to nine in that: the annealing process in step five is: keeping warm at 200 to 600° C. for 1 to 72 hours.

[0050] The following examples are used to verify the effects of the present invention:

[0051] Embodiment 1:

[0052] The preparation method of the high specific stiffness composite conductor of this embodiment is carried out according to the following steps:

[0053] Step 1: Preparation of Be / Aluminum Composite Materials

[0054] Beryllium / aluminum composite materials were prepared by self-exhaust pressure infiltration method; the specific process is as follows:

[0055] ① Weigh beryllium powder and aluminum matrix according to volume fractions of 60% and 40%, and load the beryllium powder into a steel mold and press it into a preform with a holding pressure of 50kN and a holding time of 4min. Then put the steel mold containing the beryllium powder preform into a preheating furnace and preheat it at 600℃ for 2h; ② Melt the aluminum matrix at a temperature of 880℃ to obtain liquid aluminum, and then pour the liquid aluminum into the preheated steel mold in step ①; ③ Move the pressure head downward at a pressure of 50MPa and a speed of 5mm / min to make the liquid aluminum infiltrate into the gaps of the beryllium powder, and hold the pressure at 25MPa for 3min, and then cool it with circulating water to obtain a beryllium / aluminum composite material;

[0056] The aluminum matrix is ​​Al-1.5Mg-1.5Si alloy;

[0057] The beryllium powder has a purity of 99.5% and an average particle size of 50 μm; the beryllium powder is industrial beryllium powder with irregular shape.

[0058] Step 2: Preheating of Be / Aluminum Composite Material and Hot Extrusion Die:

[0059] The beryllium / aluminum composite material is first preheated to a temperature of 540°C, and then kept at 540°C for 2 hours; the hot extrusion die is preheated to a temperature of 450°C, and then kept at the same temperature for 3 hours;

[0060] Step 3: Preparation of Be / Aluminum Composite Rods by Hot Extrusion

[0061] The preheated beryllium / aluminum composite material was loaded into a preheated hot extrusion die and hot extruded by a press at a hot extrusion rate of 50 mm / min and an extrusion ratio of 49:1 to obtain a beryllium / aluminum composite material rod with a diameter of 5 mm.

[0062] Step 4: Sheathing of Be / Aluminum Composite Bars

[0063] Heat a pure copper tube with an inner diameter of 5 mm and an outer diameter of 7 mm to 300° C., then sleeve a pure copper tube with an inner diameter the same as that of the beryllium / aluminum composite material rod obtained in step 3 on the outside of the rod, and cool naturally to room temperature to obtain a copper-clad beryllium / aluminum composite material rod;

[0064] Step 5: Preparation of copper-clad beryllium / aluminum composite conductor by hot drawing

[0065] A beryllium / aluminum composite material rod is subjected to multiple hot drawing processes using a drawing machine, the hot drawing temperature is 540°C, the deformation amount of each process is 3%, the drawing rate is 60 mm / min, and the beryllium / aluminum composite material is annealed after each deformation process to obtain a copper-clad beryllium / aluminum composite material composite wire with a diameter of 2 mm; the annealing process is: keeping warm at 495°C for 5 hours.

[0066] The density of the composite wire prepared in the embodiment is 5.49 g / cm 3 Compared with pure Cu wire, the density is reduced by 38.5%. The specific stiffness of the composite wire prepared in the embodiment is 39.4 GPa / (g / cm 3 ), the conductivity is 4.4×10 7 S / m. Figure 1 This is a spectrum scanning image of the copper element diffusing into the beryllium / aluminum composite material in this embodiment, indicating that the copper element enters the inner core of the beryllium / aluminum composite material during the hot drawing process, and the copper sheath and the inner core are metallurgically bonded.

[0067] Embodiment 2:

[0068] The preparation method of the high specific stiffness composite conductor of this embodiment is carried out according to the following steps:

[0069] Step 1: Preparation of Be / Aluminum Composite Materials

[0070] Beryllium / aluminum composite materials were prepared by self-exhaust pressure infiltration method; the specific process is as follows:

[0071] ① Weigh beryllium powder and aluminum matrix at volume fractions of 45% and 55%, and load the beryllium powder into a steel mold and press it into a preform with a holding pressure of 70kN and a holding time of 10min. Then put the steel mold containing the beryllium powder preform into a preheating furnace and preheat it at 620℃ for 2h; ② Melt the aluminum matrix at a temperature of 860℃ to obtain liquid aluminum, and then pour the liquid aluminum into the preheated steel mold in step ①; ③ Move the pressure head downward at a pressure of 30MPa and a speed of 6mm / min to make the liquid aluminum infiltrate into the gaps of the beryllium powder, and hold the pressure at 30MPa for 5min, and then cool it by circulating water to obtain a beryllium / aluminum composite material;

[0072] The aluminum matrix is ​​Al-1.2Mg alloy;

[0073] The beryllium powder has a purity of 99% and an average particle size of 80 μm; the beryllium powder is an irregularly shaped industrial beryllium powder.

[0074] Step 2: Preheating of Be / Aluminum Composite Material and Hot Extrusion Die:

[0075] The beryllium / aluminum composite material is first preheated to a temperature of 530°C, and then kept at 530°C for 2 hours; the hot extrusion die is preheated to a temperature of 440°C, and then kept at the same temperature for 3 hours;

[0076] Step 3: Preparation of Be / Aluminum Composite Rods by Hot Extrusion

[0077] The preheated beryllium / aluminum composite material was loaded into a preheated hot extrusion die and hot extruded by a press at a hot extrusion rate of 80 mm / min and an extrusion ratio of 36:1 to obtain a beryllium / aluminum composite material rod with a diameter of 4 mm.

[0078] Step 4: Sheathing of Be / Aluminum Composite Bars

[0079] Heat a pure copper tube with an inner diameter of 4 mm and an outer diameter of 6 mm to 200° C., then sleeve a pure copper tube with an inner diameter the same as that of the beryllium / aluminum composite material rod obtained in step 3 on the outside of the rod, and cool naturally to room temperature to obtain a copper-clad beryllium / aluminum composite material rod;

[0080] Step 5: Preparation of copper-clad beryllium / aluminum composite conductor by hot drawing

[0081] A beryllium / aluminum composite material rod is subjected to multiple hot drawing passes using a drawing machine, the hot drawing temperature is 520°C, the deformation amount of each pass is 4%, the drawing rate is 40 mm / min, and the beryllium / aluminum composite material is annealed after each deformation pass to obtain a copper-clad beryllium / aluminum composite material composite wire with a diameter of 1.8 mm; the annealing process is: keeping warm at 450°C for 8 hours.

[0082] The density of the composite wire prepared in the embodiment is 5.99 g / cm 3 Compared with pure Cu wire, the density is reduced by 32.9%. The specific stiffness of the composite wire prepared in the embodiment is 30.8 GPa / (g / cm 3 ), the conductivity is 4.7×10 7 S / m.

[0083] Embodiment three:

[0084] The preparation method of the high specific stiffness composite conductor of this embodiment is carried out according to the following steps:

[0085] Step 1: Preparation of Be / Aluminum Composite Materials

[0086] Beryllium / aluminum composite materials were prepared by self-exhaust pressure infiltration method; the specific process is as follows:

[0087] ① Weigh beryllium powder and aluminum matrix according to volume fractions of 40% and 60%, and load the beryllium powder into a steel mold and press it into a preform with a holding pressure of 90kN and a holding time of 3min. Then put the steel mold containing the beryllium powder preform into a preheating furnace and preheat it at 530℃ for 2h; ② Melt the aluminum matrix at a temperature of 840℃ to obtain liquid aluminum, and then pour the liquid aluminum into the preheated steel mold in step ①; ③ Move the pressure head downward at a pressure of 30MPa and a speed of 5mm / min to make the liquid aluminum infiltrate into the gaps of the beryllium powder, and hold the pressure at 30MPa for 3min, and then cool it by circulating water to obtain a beryllium / aluminum composite material;

[0088] The aluminum matrix is ​​Al-10Si alloy;

[0089] The beryllium powder has a purity of 99.6% and an average particle size of 60 μm; the beryllium powder is spherical.

[0090] Step 2: Preheating of Be / Aluminum Composite Material and Hot Extrusion Die:

[0091] First, the beryllium / aluminum composite material is preheated to a temperature of 480°C, and then kept at 480°C for 2 hours; the hot extrusion die is preheated to a temperature of 400°C, and then kept at the temperature for 3 hours;

[0092] Step 3: Preparation of Be / Aluminum Composite Rods by Hot Extrusion

[0093] The preheated beryllium / aluminum composite material was loaded into a preheated hot extrusion die and hot extruded by a press at a hot extrusion rate of 80 mm / min and an extrusion ratio of 40:1 to obtain a beryllium / aluminum composite material rod with a diameter of 5 mm.

[0094] Step 4: Sheathing of Be / Aluminum Composite Bars

[0095] Heat a pure copper tube with an inner diameter of 5 mm and an outer diameter of 8 mm to 240° C., then sleeve a pure copper tube with an inner diameter the same as that of the beryllium / aluminum composite material rod obtained in step 3 onto the outside of the rod, and cool naturally to room temperature to obtain a copper-clad beryllium / aluminum composite material rod;

[0096] Step 5: Preparation of copper-clad beryllium / aluminum composite conductor by hot drawing

[0097] A beryllium / aluminum composite material rod is subjected to multiple hot drawing passes using a drawing machine, the hot drawing temperature is 500°C, the deformation amount of each pass is 4%, the drawing rate is 10 mm / min, and the beryllium / aluminum composite material is annealed after each deformation pass to obtain a copper-clad beryllium / aluminum composite material composite wire with a diameter of 1.6 mm; the annealing process is: keeping warm at 345°C for 18 hours.

[0098] The density of the composite wire prepared in the embodiment is 6.36 g / cm 3 Compared with pure Cu wire, the density is reduced by 28.7%. The specific stiffness of the composite wire prepared in the embodiment is 27.4 GPa / (g / cm 3 ), the conductivity is 4.8×10 7 S / m.

[0099] Embodiment 4:

[0100] The preparation method of the high specific stiffness composite conductor of this embodiment is carried out according to the following steps:

[0101] Step 1: Preparation of Be / Aluminum Composite Materials

[0102] Beryllium / aluminum composite materials were prepared by self-exhaust pressure infiltration method; the specific process is as follows:

[0103] ① Weigh beryllium powder and aluminum matrix according to volume fractions of 60% and 40%, and load the beryllium powder into a steel mold and press it into a preform with a holding pressure of 100kN and a holding time of 3min. Then put the steel mold containing the beryllium powder preform into a preheating furnace and preheat it at 600℃ for 2h; ② Melt the aluminum matrix at a temperature of 840℃ to obtain liquid aluminum, and then pour the liquid aluminum into the preheated steel mold in step ①; ③ Move the pressure head downward at a pressure of 40MPa and a speed of 5mm / min to make the liquid aluminum infiltrate into the gaps of the beryllium powder, and hold the pressure at 40MPa for 5min, and then cool it by circulating water to obtain a beryllium / aluminum composite material;

[0104] The aluminum matrix is ​​Al-6.1Zn-2.9Mg alloy;

[0105] The beryllium powder has a purity of 99.7% and an average particle size of 100 μm; the beryllium powder has an irregular shape.

[0106] Step 2: Preheating of Be / Aluminum Composite Material and Hot Extrusion Die:

[0107] First, the beryllium / aluminum composite material is preheated to a temperature of 500°C, and then kept at 500°C for 2 hours; the hot extrusion die is preheated to a temperature of 450°C, and then kept at the same temperature for 2 hours;

[0108] Step 3: Preparation of Be / Aluminum Composite Rods by Hot Extrusion

[0109] The preheated beryllium / aluminum composite material was loaded into a preheated hot extrusion die and hot extruded by a press at a hot extrusion rate of 80 mm / min and an extrusion ratio of 50:1 to obtain a beryllium / aluminum composite material rod with a diameter of 3 mm.

[0110] Step 4: Sheathing of Be / Aluminum Composite Bars

[0111] Heat a pure copper tube with an inner diameter of 3 mm and an outer diameter of 5 mm to 350° C., then sleeve a pure copper tube with an inner diameter the same as that of the beryllium / aluminum composite material rod obtained in step 3 onto the outside of the rod, and cool naturally to room temperature to obtain a copper-clad beryllium / aluminum composite material rod;

[0112] Step 5: Preparation of copper-clad beryllium / aluminum composite conductor by hot drawing

[0113] A beryllium / aluminum composite material rod is subjected to multiple hot drawing processes using a drawing machine, the hot drawing temperature is 510°C, the deformation amount of each process is 5%, the drawing rate is 50 mm / min, and the beryllium / aluminum composite material is annealed after each deformation process to obtain a copper-clad beryllium / aluminum composite material composite wire with a diameter of 1.4 mm; the annealing process is: keeping warm at 435°C for 10 hours.

[0114] The density of the composite wire prepared in the embodiment is 6.50 g / cm 3 Compared with pure Cu wire, the density is reduced by 27.2%. The specific stiffness of the composite wire prepared in the embodiment is 27.2 GPa / (g / cm 3 ), the conductivity is 4.8×10 7 S / m.

[0115] Embodiment five:

[0116] The preparation method of the high specific stiffness composite conductor of this embodiment is carried out according to the following steps:

[0117] Step 1: Preparation of Be / Aluminum Composite Materials

[0118] Beryllium / aluminum composite materials were prepared by self-exhaust pressure infiltration method; the specific process is as follows:

[0119] ① Weigh beryllium powder and aluminum matrix according to volume fractions of 55% and 45%, and load the beryllium powder into a steel mold and press it into a preform with a holding pressure of 110kN and a holding time of 3min. Then put the steel mold containing the beryllium powder preform into a preheating furnace and preheat it at 550℃ for 2h; ② Melt the aluminum matrix at a temperature of 850℃ to obtain liquid aluminum, and then pour the liquid aluminum into the preheated steel mold in step ①; ③ Move the pressure head downward at a pressure of 40MPa and a speed of 5mm / min to make the liquid aluminum infiltrate into the gaps of the beryllium powder, and hold the pressure at 40MPa for 4min, and then cool it by circulating water to obtain a beryllium / aluminum composite material;

[0120] The aluminum matrix is ​​Al-4.9Mg alloy;

[0121] The beryllium powder has a purity of 99.2% and an average particle size of 300 μm; the beryllium powder is beryllium turning chip recovery powder.

[0122] Step 2: Preheating of Be / Aluminum Composite Material and Hot Extrusion Die:

[0123] First, the beryllium / aluminum composite material is preheated to a temperature of 550°C, and then kept at 550°C for 2 hours; the hot extrusion die is preheated to a temperature of 510°C, and then kept at the temperature for 3 hours;

[0124] Step 3: Preparation of Be / Aluminum Composite Rods by Hot Extrusion

[0125] The preheated beryllium / aluminum composite material was loaded into a preheated hot extrusion die and hot extruded by a press at a hot extrusion rate of 60 mm / min and an extrusion ratio of 25:1 to obtain a beryllium / aluminum composite material rod with a diameter of 6 mm.

[0126] Step 4: Sheathing of Be / Aluminum Composite Bars

[0127] Heat a pure copper tube with an inner diameter of 6 mm and an outer diameter of 10 mm to 200° C., then sleeve a pure copper tube with an inner diameter the same as that of the beryllium / aluminum composite material rod obtained in step 3 on the outside of the rod, and cool naturally to room temperature to obtain a copper-clad beryllium / aluminum composite material rod;

[0128] Step 5: Preparation of copper-clad beryllium / aluminum composite conductor by hot drawing

[0129] A beryllium / aluminum composite material rod is subjected to multiple hot drawing passes using a drawing machine, the hot drawing temperature is 450°C, the deformation amount of each pass is 3%, the drawing rate is 45mm / min, and the beryllium / aluminum composite material is annealed after each deformation pass to obtain a copper-clad beryllium / aluminum composite material composite wire with a diameter of 1mm; the annealing process is: keeping warm at 320°C for 24h.

[0130] The density of the composite wire prepared in the embodiment is 6.51 g / cm 3 Compared with pure Cu wire, the density is reduced by 27.0%. The specific stiffness of the composite wire prepared in the embodiment is 27.0 GPa / (g / cm 3 ), the conductivity is 4.8×10 7 S / m.

Claims

1. A method for preparing a high specific stiffness composite conductor, characterized in that: The preparation method of the high specific stiffness composite conductor is carried out according to the following steps: Step 1: Preparation of Be / Aluminum Composite Materials The beryllium / aluminum composite material is prepared by a self-exhaust pressure infiltration method; the volume fraction of beryllium powder in the beryllium / aluminum composite material is 20% to 70%, and the aluminum matrix in the beryllium / aluminum composite material is pure aluminum or aluminum alloy; Step 2: Preheating of Be / Aluminum Composite Material and Hot Extrusion Die First, the beryllium / aluminum composite material is preheated to a temperature of 400-600°C, and then kept at a temperature of 400-600°C for 0.5h-6h; the hot extrusion die is preheated to a temperature 10°C-100°C lower than the preheating temperature of the beryllium / aluminum composite material, and then kept at the temperature for 0.5h-6h; Step 3: Preparation of Be / Aluminum Composite Rods by Hot Extrusion The preheated beryllium / aluminum composite material is loaded into a preheated hot extrusion die, and hot extruded by a press to obtain a beryllium / aluminum composite material rod; Step 4: Sheathing of Be / Aluminum Composite Bars The pure copper tube is heated to 200-600° C., and then a pure copper tube having the same inner diameter as the beryllium / aluminum composite material rod obtained in step 3 is sheathed on the outside of the rod, and the rod is naturally cooled to room temperature to obtain a copper-sheathed beryllium / aluminum composite material rod; Step 5: Preparation of copper-clad beryllium / aluminum composite conductor by hot drawing A drawing machine is used to perform multiple hot drawing on a copper-clad beryllium / aluminum composite material rod, the hot drawing temperature is 200-600°C, the deformation amount of each pass is 1%-10%, and the drawing rate is 10-200mm / min; after each deformation, the copper-clad beryllium / aluminum composite material is annealed to obtain a copper-clad beryllium / aluminum composite material composite wire with a diameter of 0.5-2mm.

2. The method for preparing a high specific stiffness composite conductor according to claim 1, characterized in that: The beryllium powder described in step 1 has a purity greater than 99% and an average particle size of 5 to 800 μm.

3. The method for preparing a high specific stiffness composite conductor according to claim 1, characterized in that: The beryllium powder in step 1 is in the form of irregular shape, spherical shape, and beryllium turning chips, or any combination of the two.

4. The method for preparing a high specific stiffness composite conductor according to claim 1, characterized in that: The aluminum alloy described in step 1 is one of Al-Si alloy, Al-Cu alloy, Al-Mg alloy, Al-Si-Cu alloy, Al-Si-Mg alloy, Al-Cu-Mg alloy, Al-Zn-Cu alloy, Al-Zn-Mg alloy, Al-Zn-Mg-Cu alloy, Al-Be alloy, Al-Li alloy and Al-Si-Cu-Mg alloy, or any combination of several of them.

5. The method for preparing a high specific stiffness composite conductor according to claim 4, characterized in that: The mass fraction of Si in the Al-Si alloy is 0.5% to 25%; the mass fraction of Cu in the Al-Cu alloy is 0.5% to 53%; the mass fraction of Mg in the Al-Mg alloy is 0.5% to 38%; the mass fraction of Si in the Al-Si-Cu alloy is 0.5% to 25%, and the mass fraction of Cu is 0.5% to 53%; the mass fraction of Si in the Al-Si-Mg alloy is 0.5% to 25%, and the mass fraction of Mg is 0.5% to 38%; the mass fraction of Cu in the Al-Cu-Mg alloy is 0.5% to 53%, and the mass fraction of Mg is 0.5% to 38%; the mass fraction of Zn in the Al-Zn-Cu alloy is 0.5% to 55%, and the mass fraction of Cu is 0.5% to 53%. The mass fraction of u is 0.5% to 53%; the mass fraction of Zn in Al-Zn-Mg alloy is 0.5% to 55%, and the mass fraction of Mg is 0.5% to 38%; the mass fraction of Zn in Al-Zn-Mg-Cu alloy is 0.5% to 55%, the mass fraction of Mg is 0.5% to 38%, and the mass fraction of Cu is 0.5% to 53%; the mass fraction of Be in Al-Be alloy is 0.5% to 20%; the mass fraction of Li in Al-Li alloy is 0.5% to 35%; the mass fraction of Si in Al-Si-Cu-Mg alloy is 0.5% to 25%, the mass fraction of Cu is 0.5% to 53%, and the mass fraction of Mg is 0.5% to 38%.

6. The method for preparing a high specific stiffness composite conductor according to claim 1, characterized in that: The hot extrusion rate in step 3 is 30 mm / min to 120 mm / min.

7. The method for preparing a high specific stiffness composite conductor according to claim 1, characterized in that: The extrusion ratio of the hot extrusion in step 3 is (5-58):

1.

8. The method for preparing a high specific stiffness composite conductor according to claim 1, characterized in that: The inner diameter of the pure copper tube in step 4 is 1 to 15 mm, and the outer diameter is 2 to 30 mm.

9. The method for preparing a high specific stiffness composite conductor according to claim 1, characterized in that: Step 5: Use a drawing machine to perform multiple hot drawing on the beryllium / aluminum composite material rod, the hot drawing temperature is 540°C, the deformation amount of each pass is 3%, the drawing rate is 60mm / min, and the beryllium / aluminum composite material is annealed after each deformation to obtain a copper-clad beryllium / aluminum composite material composite wire with a diameter of 2mm; the annealing process is: keep warm at 495°C for 5h.

10. The method for preparing a composite conductor with high specific stiffness according to claim 1, characterized in that: The annealing process in step 5 is: keeping the temperature at 200-600° C. for 1-72 hours.

Citation Information

Patent Citations

  • Aluminum alloy for electric conductors and its method of manufacture

    CA1041797A

  • Beryllium-aluminum alloy sheet and manufacturing method thereof

    CN104942271A

  • Preparation method of copper-aluminum composite wire

    CN109801756A

  • Preparation method of beryllium-aluminum alloy surface composite reinforced modified layer

    CN113502443A

  • Method for preparing and molding high-toughness beryllium / aluminum composite material through semi-solid plastic deformation

    CN115305375A